Chronological Tables for Caesar’s Wars (58–45 BCE) - Ramsey, John T.; Raaflaub, Kurt A. (Histos, 2018)
This chronological outline of Julius Caesar's campaigns in Gaul and during the civil wars is the first of its kind in coverage and depth. Never before have the years 58-50 BCE been parsed in such detail. For an account of how the dates in that period were determined, the reader is referred to Histos 11 (2017) 1-74. The tables covering the years 49-45 expand and refine previously published outlines of this sort, virtually all of which rely to some extent on Colonel Eugène Stoffel's 'Tableau de Dates', first published in vol. 2 of his Histoire de Jules César: Guerre Civile (Paris, 1887) 421-38. A fresh analysis, taking advantage of subsequent scholarship and using modern digital maps based on a GIS interface, has made it possible to refine data and arrive at a more securely grounded reconstruction of Caesar's movements and the sequence of events in his wars and campaigns. This improved presentation of chronology gives us a better understanding of the course of history in those years by synchronizing events in the field with political developments in Rome and happenings elsewhere in the Roman empire.